Whole‐genome SNP data unravel population structure and signatures of selection for black plumage of indigenous chicken breeds from Jiangxi province, China. (15th July 2019) - Mao, H.; Wang, X.; Fan, Y.; Cheng, D.; Chen, K.; Liu, S.; Xi, S.; Wan, L.; Li, X.; Ren, J.
Summary: Ten indigenous chicken breeds were originally distributed in Jiangxi Province, China, and they define a critical component of Chinese chicken genetic resources. We have investigated the population genetics of seven Jiangxi chicken breeds using 600K chicken BeadChip SNP data. To provide a genome‐wide perspective for the population structure of all 10 Jiangxi chicken breeds, we herein genotyped 78 additional individuals from the seven breeds and 63 chickens from three uninvestigated breeds—Yugan Black (YG), Nancheng Black (NC) and Wanzai Yellow using 55K chicken SNP arrays. We then explored merged data of 17 101 SNPs from 235 individuals to infer the population structure of the 10 breeds. We showed that NC and YG are two regional populations of the same breed, as individuals from the two populations clustered together to form a branch separate from the other breeds in the neighbor‐joining tree, they always grouped together in multidimensional principal component analyses and they displayed an identical pattern of ancestral lineage composition. Hence, NC and YG should be considered a single breed in the state‐supported conservation scheme. Moreover, we conducted a genome scan for signatures of selection for black plumage.bayescan andhapflk analyses of two contrasting groups (three black‐feathered breeds vs. six non‐black‐feathered breeds) consistently detected 25 putative regions under selection. Nine pigmentation‐ associated genes ( DCT, SLC24A5, SLC30A4, MYO5A, CYP19A1, NADK2, SLC45A2, GNAQ and DCP2 ) reside within these regions, and these genes are interesting candidates for black plumage and provide a starting point for further identification of causative mutations for black feathers in chicken.